Biofilm formation and electron transfer in bioelectrochemical systems. Issue 1 (1st January 2018) - Sevda, Surajbhan; Sharma, Swati; Joshi, Chetan; Pandey, Lalit; Tyagi, Namrata; Abu-Reesh, Ibrahim; Sreekrishnan, T.R.
ABSTRACT: In the recent years, considerable body of research has been carried out in the field of bioelectrochemical systems (BESs) for treatment of wastewater and generation of power. In these systems, different microbes are used for carrying out the transfer of electrons from medium to the anode electrode. The microbes employed are known as electrogens as they have the capacity to transfer electrons. Bacteria such as those belonging to the species such as Geobacter, Betaproteo, Deltaproteo and Desulfurnonas and of genus Shewanella are the commonly explored electrogens in BESs. In the past few years, a renewed interest in microbial fuel cell (MFC) research has developed, yet power generated from these devices has not significantly advanced. The primary reason for this non-advancement is that the research is more focused on improving power generation rather than on elementary understanding of the electron transfer processes. This review focuses on the methods used to study electron transfer processes in biofilms growing on the electrodes and presents several successful applications of MFCs. In this review, we have defined electrochemically active biofilms as biofilms that exchange electrons with conductive surfaces called electrodes. GRAPHICAL ABSTRACT: